Juridical Analysis of Blocking Sabh Access In The RI Ministry of Minority Shareholders As a Form of Legal Protection of Minority Shareholders - Juanito, Alfvino (Dinasti Research, 2024)
Legal subject on a protection for minority shareholders is less attendance whether in the formulation of legal theories, or law making process in Indonesia. Prevailing laws and regulations are deemed unable to provide effective protection to legal interests of the shareholder minority. Apart from the right to file derivative action in accordance with Article 61 of Indonesian Company Law, there is a provision under Ministry of Law and Human Rights Decision No. 29/2022 that stipulating the protection to minority shareholder under dispute to file for blocking company's access to the Legal Entity Administration System on the Directorate General of General Legal Administration of the Ministry of Law and Human Rights of the Republic of Indonesia (SABH). The research shows that there is an impact when such a company's access to SABH is blocked, then such a company is denied to process business license; as a consequence of such integration between SABH and Indonesia' business licensing system that is centralized under the Online Single Submission system (OSS). When such company's access to SABH is blocked, access to OSS will also be blocked due to failures on verification process during login to OSS, and there will be notifications on OSS “Login Failed, Please Call SABH”. Thus, such companies are denied to process any business license within the OSS. Furthermore, the research shows there is a case that a minority shareholder who filed for SABH blocking, was charged for committing an unlawful act. For the sake of legal certainty, justification must be carried out for the implementation of protection to minority shareholder rights based on the provisions of the applicable laws and regulations, in this case as specified under PermenkumHAM 29/2022; in furtherance as impact from denied access to process any business license caused by such company's SABH blocked